Maternally Expressed Gene 3 Negatively Regulated Decorin to Supresse Angiogenesis, Proliferation and Migration of Endothelial Cells - Dai, Dongwei; Zhang, Lei; Li, Jin; Di, Yunhai; Tian, Chun'ou; Liu, Jianmin; Hong, Bo (Current molecular medicine, 2023)
Angiogenesis of tumor cells is highly associated with tumorsecreted factors and matrix proteins. However, the underlying mechanism of tumorsecreted factors and matrix proteins during angiogenesis is rarely discussed. This study investigated the relationship between the maternally expressed gene 3 (MEG3), a tumor-secreted growth factor, and Decorin, a tumor-secreted matrix protein, and evaluated their derivate roles in human endothelial cell development. Human endothelial cells were transiently transfected with a plasmid expressing antisense of Decorin mRNA (shDecorin) and silencing mRNA of MEG3 (siMEG3) or MEG3 over-expressive vectors. A series of qPCR and Western blot analysis was applied to characterize the expressions of MEG3 and Decorin in all transfected cells. Moreover, scratch, Transwell, and Matrigel neovascularization assays were performed to examine three key processes of endothelial cells' angiogenesis, including tubulogenesis, proliferation, and migratory levels. In addition, the cell viability was evaluated at each step via the MTT test. The overexpression of MEG3 inhibited angiogenesis and migration of endothelial cells by preventing the expression of Decorin. At the same time, the inhibition of MEG3 via siRNA resulted in an increased expression of Decorin, enhanced tube formation levels, and promoted endothelial cell proliferation and migration. Furthermore, Decorin's knockdown suppressed the angiogenesis and migration of endothelial cells without affecting the expression of MEG3. Importantly, the stimulation of HUVEC cells with exogenous Decorin protein alleviated most phenotypes induced by the upregulation of MEG3. Our study demonstrated the anti-growth effects of MEG3 on vasculogenesis and migration of endothelial cells. Thus, by blocking the expression of Decorin in HUVECs, the overexpression of MEG3 repressed their development and might potentially alleviate the ischemic stroke.